Influences on limited antimicrobial use in small-scale freshwater aquaculture farms in central Thailand - Alhusein, Nour; Chantong, Boonrat; Suwanpakdee, Sarin; Wiratsudakul, Anuwat; Gould, Virginia C.; Wichuwaranan, Kantima; Poonsawad, Kornrawan; Montrivade, Varapon; Charoenboon, Nutcha; Sringernyuang, Luechai; Avison, Matthew B.; Lambert, Helen; et al. (Frontiers in Veterinary Science, 2025)
IntroductionRecent years have shown substantial growth both in the scale and the spread of freshwater aquaculture in Thailand, raising concerns about potential widespread unsustainable use of antimicrobials.MethodsThis mixed-methods study used surveys and qualitative interviews to examine conditions of freshwater aquaculture farming in central Thailand in relation to animal health, disease management and patterns of antimicrobial use.ResultsFreshwater aquaculture in this area of Thailand was largely a domestic venture operated as a source of additional household income to increase financial security. Aquaculture was often integrated with other types of farming; initial outlay was reduced by repurposing unused crops, food, or animal manure (e.g. chicken droppings and pig dung) to fertilise aquaculture ponds. Among farmers representing twenty farms who were surveyed during 2019, only six farmers representing six farms said they used antimicrobials. These included oxytetracycline, enrofloxacin, norfloxacin, ciprofloxacin and sulphonamides. Farmers doubted the benefits of using antimicrobials to treat aquatic animals; some believed antimicrobials stunted growth. The high cost of medicines and prohibitive regulations also discouraged antimicrobial use. Farmers linked disease occurrence to changes in the weather, the emergence of new diseases and variable water quality. They relied on farm management practices to maintain the health of their aquatic animals, using lime and salt to maintain and improve water quality and pH and to disinfect aquaculture pools. Farmers also reported obtaining juvenile fish and shrimp selectively from farms known to produce healthy stock. Specialised veterinary services for aquatic farming were rare, so farmers relied on their own experimentation with medicines, peer advice and recommendations of shopkeepers who sold both aquatic feed and medicines.ConclusionThis study unexpectedly reveals limited use of antimicrobials linked to socio-economic and ecological features of small-scale family aquaculture farms.